1998
DOI: 10.1590/s1415-47571998000300021
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome damage induced by DNA topoisomerase II inhibitors combined with g-radiation in vitro

Abstract: Combined radiation and antineoplastic drug treatment have important applications in cancer therapy. In the present work, an evaluation was made of two known topoisomerase II inhibitors, doxorubicin (DXR) and mitoxantrone (MXN), with g-radiation. The effects of DXR or MXN on g-radiation-induced chromosome aberrations in Chinese hamster ovary (CHO) cells were analyzed. Two concentrations of each drug, 0.5 and 1.0 µg/ml DXR, and 0.02 and 0.04 µg/ml MXN, were applied in combination with two doses of g-radiation (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Other studies also demonstrated an interaction of different agents, including secondary metabolites and crude extracts of plants, resulting in enhanced risk for genotoxicity (Ansah et al 2005;Araújo et al 1998), similar to the organic tomato extract that enhanced genotoxicity induced by DXR in the Drosophila wing spot test (Dutra et al 2009). …”
Section: Discussionmentioning
confidence: 94%
“…Other studies also demonstrated an interaction of different agents, including secondary metabolites and crude extracts of plants, resulting in enhanced risk for genotoxicity (Ansah et al 2005;Araújo et al 1998), similar to the organic tomato extract that enhanced genotoxicity induced by DXR in the Drosophila wing spot test (Dutra et al 2009). …”
Section: Discussionmentioning
confidence: 94%
“…In agreement with all these observations, the cytotoxic and genotoxic effects of these b-carboline alkaloids have been related to their injurious action on DNA (Sasaki et al 1992;Shimoi et al 1992;Meester 1995;Picada et al 1997) because of the intercalation of DNA (Meester 1995;Taira et al 1997;Balon et al 1999). Intercalating agents such as acridine and quinacrine stains, as well as antineoplastic agents, can induce chromosome aberrations and DNA strand breaks in mammalian cells (De Marini & Laurence 1992;Suzuki et al 1995;Araú jo et al 1998;Palitti 1998). Moreover, many intercalating agents are DNA topoisomerase inhibitors and can interfere with the breakage-rejoining action of these enzymes, resulting in the formation of complexes between enzyme and DNA, favoring DNA strand breaks (Chen & Liu 1994;Wang 1996Wang & 1998Hammonds et al 2000).…”
Section: Discussionmentioning
confidence: 78%